Elevation of Peripheral Blood CD34+ and Platelet Levels After Exercise With Cooling and Compression - Mark C. Callanan, M.D; Kevin D. Christensen, M.D; Hillary A. Plummer, Ph.D., A.T.C; Johnny Torres, B.S; Adam W. Anz, M.D (Elsevier, 2021)
Purpose: To analyze the cellular response and chemokine profiles following exercise using cooling and blood flow restriction on the Vasper system. Methods: Healthy male patients between the ages of 20 and 39 years were recruited. Testing was performed on the Vasper system, a NuStep cross-trainer with concomitant 4-limb venous compression with proximal arm cuffs at 40 mm Hg and proximal leg cuffs at 65 mm Hg. A cooling vest and cooling mat (8.3°C) were used. A 7-minute warm-up followed by alternating 30- and 60-second sprints with 1.5 and 2 minutes of active recovery, respectively, between each sprint. Peripheral blood was drawn before exercise, immediately following exercise (T20), 10 minutes after the first post-exercise blood draw (T30), and then every 30 minutes (T60, T90, T120, T150, T180). A blood draw occurred at 24 hours' postexercise. Complete blood count, monoclonal flow cytometry for CD34+, and enzyme-linked immunosorbent assay were used to analyze the samples. Results: Sixteen healthy male patients (29.5 ± 4.5years, 1.78 ± 0.05m, 83.7 ± 11.4 kg) were enrolled. There was an immediate, temporary increase in white blood cell counts, marked by an increase in lymphocyte differential (38.3 ± 6.5 to 44.3 ± 9.0%, P = .001), decrease in neutrophil differential (47.8 ± 6.6 to 42.0 ± 9.1%, P < .001), and platelets (239.5 ± 57.2 to 268.6 ± 86.3 K⋅μL-1, P = .01). Monocytes significantly decreased from PRE to T90 (9.8 ± 1.1 to 8.9 ± 1.1K/μL, P < .001) and T120 (8.9 ± 1.1 K/μL, P < .0001). There was a significant increase in CD34+ cells (3.9 ± 2.0 to 5.3 ± 2.8 cells⋅μL-1, P < .001). No detectable differences in measured cytokine levels of interleukin (IL)-10, IL-6, granulocyte-macrophage colony-stimulating factor , IL-1ra, tumor necrosis factor-α, or IL-2 were observed. Conclusions: A significant elevation of peripheral blood CD34+ and platelet levels immediately following the exercise session was observed; however, there was no effect on peripheral circulation of IL-10, IL-6, IL-1ra, tumor necrosis factor-α, or IL-2. Clinical Relevance: Exercise can be considered as a way to manipulate point-of-care blood products like platelet-rich plasma and may increase product yield.